2020
DOI: 10.1177/1708538120937127
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative cardiovascular complications rate and activity of coagulation and fibrinolysis among patients undergoing vascular surgery for peripheral artery disease and abdominal aortic aneurysm

Abstract: Objectives To compare preoperative coagulation and fibrinolysis activity and incidence of perioperative complications between patients undergoing vascular procedures for peripheral artery disease and abdominal aortic aneurysm. Methods This is a substudy of a prospective observational cohort study (VISION; NCT00512109) in which we recruited patients aged ≥45 years, undergoing surgery for peripheral artery disease and abdominal aortic aneurysm. Blood samples were obtained 24 h preoperatively to measure platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Furthermore, a recent randomized controlled trial has shown elevated levels of vWF in induced DM/HC (diabetes mellitus/hypercholesterolemia) swine, which developed atherosclerosis, suggesting that vWF might be a potential marker of endothelial dysfunction in people with metabolic syndrome [ 135 , 136 ].…”
Section: Coagulation Factors As Markers Of Risk In Peripheral Artery ...mentioning
confidence: 99%
“…Furthermore, a recent randomized controlled trial has shown elevated levels of vWF in induced DM/HC (diabetes mellitus/hypercholesterolemia) swine, which developed atherosclerosis, suggesting that vWF might be a potential marker of endothelial dysfunction in people with metabolic syndrome [ 135 , 136 ].…”
Section: Coagulation Factors As Markers Of Risk In Peripheral Artery ...mentioning
confidence: 99%